Molecular genetic characteristics of elderly patients with lung adenocarcinoma - LIU Jue, XU Rui, SUN Youwei (Xin yixue)
Objective Using the NGS sequencing data to analyze the molecular genetic characteristics and correlation of elderly lung adenocarcinoma patients， to provide clinical evidence for targeted therapy. Methods 333 elderly （≥ 65-years-old） lung adenocarcinoma patients who were treated at Shandong Provincial Hospital Affiliated to Shandong First Medical University from January 2021 to December 2023 were selected as the study subjects. All patients were confirmed by surgical pathology， and the data were obtained from tissue specimen tissue testing results before initial treatment. Using the NGS platform for multi-gene mutation detection， including the nine driving genes recommended for detection in the“Chinese Medical Association Guideline Clinical Diagnosis and Treatment of Lung Cancer （2023 edition）”. Specifically EGFR， ALK， ROS1， KRAS， BRAF， ERBB2， RET， MET and NTRK， which analyzed the retrospective analysis of patient demographics， clinical pathology， and driving gene mutation status. Results The total positive rate of 9 driving genes was 41.14% （137 cases）， among which EGFR was the main driving gene with a mutation frequency of 36.04% （120 cases）， other mutation frequency genes： KRAS 15.92% （53 cases）， ERBB2 （HER2） 2.10% （7 cases）， EML4-ALK 1.80% （6 cases）， BRAF 1.50% （5 cases）， MET 1.20% （4 cases）， and RET 0.30% （1 case）. The results showed that 13 rare types of co-mutations with driver genes were concentrated in three co-mutation forms such as EGFR， KRAS， and TP53. PIK3CA， U2AF1， and BRCA1 only appeared in co-mutation form， PTEN only showed EGRF co-mutation form， and BRCA1， STK11， ARID1A， and NRAS only showed KARS co-mutation form. Through bioinformatics statistical analysis of lung adenocarcinoma data in the TCGA database， it was found that 13 rare mutated genes had high NES scores in tumor related signaling pathways， indicating their involvement in the occurrence and development of tumors. Conclusions By analyzing the molecular genetic characteristics and mutation gene correlation of elderly lung adenocarcinoma patients， the molecular genetic data of 9 recommended driving genes could reflect the distribution and correlation of driving genes in lung adenocarcinoma. Especially， further understanding of the distribution of rare genes will be more conducive to guiding clinical treatment.